Perlindungan Hukum Pada Konsumen Dalam Transaksi Jual Beli Onlinee-Commerce Ferry Irawan Febriansyah - Febriansyah, Ferry Irawan (Legal Standing : Jurnal Ilmu Hukum, 2017)
Globalization era forms society character being advanced. People often do buying and selling activities in an easy way, which is in the form of buying and selling goods in the internet or online. It is called as online commerce or e-commerce. Using online-commerce, people do not need to go out to spend their time buying for their living goods. Online-commerce facilitates people easily in trading. Saving time is becoming a reason for them to do online commerce. The method used in online-commerce is almost the same as offline commerce. Online commerce offers a lot of convenience for both sellers and buyers in transaction. This certainly has a lot of convenience, but it also has weaknesses in online transactions. For consumers, they get less-notice for protection so that online-commerce has a lot of weaknesses in this case. The Unitary State of the Republic of Indonesia is a legal state that protects the whole of Indonesia's blood spill. The State becomes a protector of its citizens in the context of consumer protection. The law has arranged that consumers also have protection in order not to cause any harm in transaction. Both offline and online transactions are regulated by consumer protection laws because these laws are intended to protect consumers in buying and selling transactions. In the law number 8 of 1999 concerning Consumer Protection is mentioned in article 1, paragraph 2, that the Customer is any user of goods and/ or services available in the community, whether for self-interest, family, other people or other living beings and not to be traded, whereas in Article 1 paragraph 1 mentioned, Consumer protection is any effort that ensures the legal certainty to give to the consumer. There are several consumer rights protected by law, such as, in article 4 of the consumer protection law including, the right to convenience, security and safety in consuming goods and / or services, the right to choose goods and/ or services and right to obtain goods and/ or services in accordance with exchange rates and the promised conditions and warranties, the right to true, clear and honest information about the conditions and warranties of goods and / or services, the right to be heard and to complain of goods and / or services used, the right to advocacy, protection and appropriate dispute resolution of consumer protection, the right to counsel and education of consumers, the right to be treated or served properly and honestly and non-discriminatively, the right to compensation and / or reimbursement , if the goods and / or services received are not in accordance with the agreement or not as appropriate, and the last is the rights set in the provisions of other legislation.The consumers’ rights that have been regulated in the law are providing legal protection to the consumer either online transaction or offline transactions. Based on the law of protection to the consumer in the context of online-commerce, the consumers can apply this law to sue their rights that have been mandated in the law as a form of legal protection to consumers.